2004
DOI: 10.1016/j.ssc.2004.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Conductance properties of nanotubes coupled to superconducting leads: signatures of Andreev states dynamics

Abstract: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscriptionConductance properties of nanotubes coupled to superconducting leads: signatures of Andreev states dynamics

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
3
12
1
Order By: Relevance
“…4, the supercurrent peak near zero bias starts to develop before any signs of higher order Andreev peaks. This seems to contradict with the scenario of Vecino et al [8] who argue that inelastic processes enhance conductance due to higher order MAR processes and lead to IV curves with hysteresis at small bias.…”
Section: H Y S I C a L R E V I E W L E T T E R Scontrasting
confidence: 68%
See 1 more Smart Citation
“…4, the supercurrent peak near zero bias starts to develop before any signs of higher order Andreev peaks. This seems to contradict with the scenario of Vecino et al [8] who argue that inelastic processes enhance conductance due to higher order MAR processes and lead to IV curves with hysteresis at small bias.…”
Section: H Y S I C a L R E V I E W L E T T E R Scontrasting
confidence: 68%
“…Enhanced conductance was observed by Buitelaar et al [7] near zero bias, which was interpreted in terms of multiple Andreev reflections (MAR) in the presence of inelastic processes [8]. Similar results were obtained by Kasumov et al [3].…”
supporting
confidence: 74%
“…On the other hand, in some experiments the zero bias conductance was observed to increase, though no supercurrents were reported [25]. Similar results were obtained for multiwall carbon nanotubes [22,26,27]. Initial experimental study in our group showed that the critical current in cuprate superconductors increases when they were mixed with CNTs.…”
Section: Introductionsupporting
confidence: 64%
“…A similar analysis of a zero bias conductance peak as supercurrent has successfully been carried out for an open quantum dot [11], i.e., without Coulomb blockade effects. We note that an alternative interpretation of the origin of the zero bias peak based on quasiparticle current (multiple Andreev reflections) with a cut-off for higher order multiple Andreev reflection processes has also been suggested [31], but in this article the supercurrent interpretation will be pursued. The value of the measured supercurrent is The suppression is partly explained within an extended resistively and capacitively shunted junction model due to interaction of the SWCNT Josephson junction with its electrical environment.…”
Section: Sub-gap Structure and Supercurrentmentioning
confidence: 99%